2018
DOI: 10.1021/acs.jafc.8b03069
|View full text |Cite
|
Sign up to set email alerts
|

Impact of n-3 Docosapentaenoic Acid Supplementation on Fatty Acid Composition in Rat Differs Depending upon Tissues and Is Influenced by the Presence of Dairy Lipids in the Diet

Abstract: The n-3 docosapentaenoic acid (n-3 DPA) could be a novel source of n-3 long-chain polyunsaturated fatty acids (LCPUFA) with beneficial physiological effects. Following the supplementation of 0.5% purified n-3 DPA for 3 weeks from weaning, the n-3 DPA content increased in one-half of the 18 studied tissues (from +50% to +110%, p < 0.05) and mostly affected the spleen, lung, heart, liver, and bone marrow. The n-3 DPA was slightly converted into DHA (+20% in affected tissues, p < 0.05) and mostly retroconverted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…EPA is mostly studied and described to inhibit inflammation, cholesterol crystal formation, to reduce oxidative properties of atherogenic lipoproteins and to increase plaque instability (reviewed in References [88,89]). DPA can be metabolized to DHA and EPA [90] and also exhibits positive effects on cardio-metabolic parameters and improves lipid metabolism in mice [91,92]. DPA is less-extensively studied owing to the price and availability of the pure compound.…”
Section: Omega 3 Fatty Acidsmentioning
confidence: 99%
“…EPA is mostly studied and described to inhibit inflammation, cholesterol crystal formation, to reduce oxidative properties of atherogenic lipoproteins and to increase plaque instability (reviewed in References [88,89]). DPA can be metabolized to DHA and EPA [90] and also exhibits positive effects on cardio-metabolic parameters and improves lipid metabolism in mice [91,92]. DPA is less-extensively studied owing to the price and availability of the pure compound.…”
Section: Omega 3 Fatty Acidsmentioning
confidence: 99%
“…The dietary impact related to different organ functions might demand special attention [66,67]. It has been suggested that the heart would be sensitive to LA concentrations by interfering with SERCA2 activity [53,54].…”
Section: Plos Onementioning
confidence: 99%
“…For example, intake of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the population is insufficient. These deficiencies may have negative effects on brain function, which may increase the risk of Alzheimer's disease in the elderly or the risk of cardiovascular or osteoarticular diseases [133][134][135]. Organic milk has been shown to be a more valuable source of EPA, DHA, and alpha-linolenic acid, even in winter [53].…”
Section: Fatty Acidsmentioning
confidence: 99%